Suicide in schools a practitioner's guide to multi-level prevention, assessment, intervention, and postvention - Erbacher, Terri A.; Singer, Jonathan B.; Poland, Scott (New York Routledge, 2015)
Suicide in Schools provides school-based professionals with practical, easy-to-use guidance on developing and implementing effective suicide prevention, assessment, intervention and postvention strategies. Utilizing a multi-level systems approach, this book includes step-by-step guidelines for developing crisis teams and prevention programs, assessing and intervening with suicidal youth, and working with families and community organizations during and after a suicidal crisis. The authors include detailed case examples, innovative approaches for professional practice, usable handouts, and internet resources on the best practice approaches to effectively work with youth who are experiencing a suicidal crisis as well as those students, families, school staff, and community members who have suffered the loss of a loved one to suicide. Readers will come away from this book with clear, step-by-step guidelines on how to work proactively with school personnel and community professionals, think about suicide prevention from a three-tiered systems approach, how to identify those who might be at risk, and how to support survivors after a traumatic event--all in a practical, user-friendly format geared especially for the needs of school-based professionals.
Foreword / Mennuti and Christner -- 1. Overview and introduction -- 2. Training gatekeepers -- 3. School crisis response planning -- 4. School liability and implications for best practice -- 5. Evidence-based suicide prevention programs -- 6. Guidelines for suicide risk assessment -- 7. Intervening with a potentially suicidal student -- 8. The aftermath: immediate suicide postvention step by step -- 9. The bereaved student, school, and community -- 10. Caring for the caregiver: burnout, compassion fatigue, and vicarious traumatization -- 11. Comprehensive case study -- 12. Suicide and schools: resources
Includes bibliographical references and index.
Keywords: Youth -- Suicidal behavior -- United States; Students -- Suicidal behavior -- United States; Suicide -- United States -- Prevention; Educational counseling -- United States; Youth -- Suicidal behavior -- United States -- Case studies; Students -- Suicidal behavior -- United States -- Case studies; Suicide -- United States. -- Prevention -- Case studies